Description Of Students' Critical Thinking Skills In Solving Relation And Function Problems - Anggara, Erwin; Tahmir, Suradi; Andi Quraisy (Universitas Islam Ahmad Dahlan (UIAD), 2023)
This research aims to describe the level of students' problem solving abilities in relation and function questions. Using a qualitative approach, data was obtained from tests and interviews. The test instrument measures critical thinking abilities. Three subjects were selected with different levels of ability: high, medium, and low. The research results show that the critical thinking ability of high ability subjects includes all indicators of critical thinking including interpretation, analysis, evaluation and inference; the medium ability subject includes 3 indicators of critical thinking ability including interpretation, analysis and inference; and for low ability subjects only on interpretation indicators.